PENGARUH MINAT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ESTIMASI BIAYA KONSTRUKSI DIMASA PANDEMI COVID 19 DI SMK NEGERI 1 PADANG - Dinna Luantika; Nurhasan Syah (Jurnal Applied Science in Civil Engineering, 2022)
This study aims to determine the effect of interest on student learning outcomes in the subject of Construction Cost Estimation during the covid 19 pandemic class XII competence in Construction and Property Business skills at SMK Negeri 1 Padang. This research is descriptive with a quantitative approach. Data collection techniques in this study using the method of distributing questionnaires. While the samples in this study were taken from all populations, namely class XII students of Construction and Property Business Skills Competence at SMK Negeri 1 Padang with a total of 48 students. The results of the research conducted from the correlation test are known if R_(count ) for interest (X) and learning outcomes (Y) is 0.405 R_(table ) 0.284, it can be concluded that there is a correlation between interest (X) and learning outcomes (Y) and the criterion of the strength of the relationship is moderate. Meanwhile, from the results of the t-test analysis, it is known that if t_(count) (3.005) than t_(table) (1.677) with a significant level of 0.05 then Ho is therefore rejected. Then from testing the coefficient of determination, it can be seen that the result is 0.405 or equal to 16.4% which is indicated by R square (the correlation number squared), meaning that the effect of X (interest) on Y (Learning Outcomes) is 16.4% while 83.6% is influenced by other factors so that it can be said that there is a weak influence between interest on student learning outcomes.